Annual Plan Proposals 1995-96 Government of Kerala - Planning Commission (Planning Commission, 1994)
It will be seen that in terms of current prices, the plan performance of the State has been showing good improvement from year to year, and it is expected that in the current year also, the State plan outlay target would be fully achieved. It may, however, be pointed out that though in terms of current prices while plan expenditure in the first three years would amount to about Rs.3100 crores, in real terms, it would be somewhat less. Since, however, it would be a difficult task to mobilise resources of the required magnitude, the State is compelled to set the sights a little lower. The size of the next year’s Annual Plan had, therefore, to be fixed at a level of Rs.1550 crores, which is 23 per cent higher than the current year’s level of Rs. 1260 crores.
State Planning Board
State Planning Board Government of Kerala